Deep eutectic solvent mediated synthesis and fabrication of a WO3–MgO nanocomposite as an electrode material for energy storage applications. (16th January 2023) - Joel, C.; Bennie, R. Biju; Antony, A. Jerold; Paul Raj, A. Nirmal; Selvakumar, G.
Abstract : WO3 –MgO nanocomposite prepared using Deep Eutectic solvents has been fabricated into device suitable for energy storage applications. Abstract : Deep eutectic solvents (DESs), a new class of ionic liquids, have been considered to be the focus of researchers owing to their wide range of applications as green solvents. These solvents are involved in changing the size and morphology of nanomaterials during their synthesis. In this work, we have synthesised WO3 –MgO nanocomposite using a DES prepared from cetyltrimethylammonium bromide (CTAB), urea and glycerol, which proved to enhance the pore volume of the composite. The X-ray diffraction peak patterns revealed a monoclinic arrangement for WO3 and cubic for MgO. The morphological and surface characterization studies were performed using scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectra and adsorption-desorption isotherms. The crystal qualities were obtained from Raman spectra and the band gap energy of WO3 increased upon forming a composite with MgO. The temperature dependent electrical conductivities and the dielectric and electric modulus properties of WO3 –MgO were studied and from electrochemical studies, the specific capacitance value obtained was 272.5 F g −1 at a current density of 1 A g −1 .